Peningkatan Hasil Belajar Peserta Didik pada Pembelajaran Pendidikan Pancasila dengan Menggunakan Model Pembelajaran Learning Cycle 7E di Kelas IV SDN 11 Campago Guguk Bulek Kota Bukittinggi - Safirti, Rani; Rahmatina, Rahmatina (TSAQOFAH, 2025)
This study is motivated by the low learning outcomes of students caused by the teachers' suboptimal use of innovative learning models during the learning process. The use of conventional methods that are one-way results in a lack of student engagement. The purpose of this study is to describe the improvement of learning outcomes in Pancasila Education through the application of the learning cycle 7E model in the fourth grade at SDN 11 Campago Guguk Bulek, Bukittinggi City. This research is a Classroom Action Research (CAR) that integrates qualitative and quantitative approaches. The research was conducted in two cycles, with Cycle I consisting of two meetings and Cycle II consisting of one meeting. Each cycle includes four stages: planning, implementation, observation, and reflection. The subjects of the study are the teacher and 27 fourth-grade students, consisting of 11 male students and 16 female students. Data collection techniques include both test and non-test techniques. The results of the study show improvements in: a) The learning module in Cycle I with an average of 87.5% (qualification B: Good), increasing to 97.22% (qualification SB: Very Good) in Cycle II; b) The implementation of learning from the teacher's aspect in Cycle I with an average of 83.33% (qualification B: Good), increasing to 94.44% (qualification SB: Very Good) in Cycle II, while the implementation of learning from the students' aspect also increased from 83.33% (qualification B: Good) in Cycle I to 94.44% (qualification SB: Very Good) in Cycle II; c) Students' learning outcomes improved from an average of 76.56% (qualification C: Satisfactory) in Cycle I to 89.33% (qualification B: Good) in Cycle II. Based on these results, it can be concluded that the application of the learning cycle 7E model is effective in improving learning outcomes in Pancasila Education among students.